FLORISTIC-STRUCTURAL CHARACTERIZATION OF DEGRADED FOREST IN THE ARC OF DEFORESTATION, BRAZILIAN AMAZON - Tramontina, Juliana; Kuplich, Tatiana (Floresta, 2024)
Floristic-structural characterization of degraded forest in the arc of deforestation, Brazilian Amazon. The purpose of this study was to characterize the floristic-structural aspects and the distribution of aboveground biomass (AGB) of degraded forests located in the arc of deforestation, southern Brazilian Amazon. In addition to characterizing the forest as a whole, analyses at the level of sampling units were established. Forest inventory data provided support to biomass estimates, as well as floristic-structural analysis. A survey was carried out, collecting from plots of 2,500 m² (50 x 50m) diameter at breast height (DBH >10cm) and total height (HT) of the trees. The forest showed a high concentration of species distributed in a few botanical families and a high number of locally rare species. The sampling units showed floristic similarity, identifiable by cluster analysis. On the other hand, they showed significant structural differences based on the DBH and HT variables. The AGB estimate for the area was 215.20 Mg ha-1 (± 83.73 Mg ha-1). Those results contribute to better understanding the changes in forest formations related to forest degradation in the southern Brazilian Amazon, as well as to the definition of conservation and restoration strategies for degraded forests.